Conductance of a phenylene-vinylene molecular wire: Contact gap and tilt angle dependence - RUNGGER, IVAN; SANVITO, STEFANO (My University, 2010)
Charge transport through a molecular junction comprising an oligomer of p-phenylene-vinylene between gold contacts has been investigated using density-functional theory and the nonequilibrium Green?s function method. The influence of the contact gap geometry on the transport has been studied for elongated and contracted gaps, as well as various molecular conformations. The calculated current-voltage characteristics show an unusual increase in the low bias conductance with the contact separation. In contrast, for compressed junctions the conductance displays only a very weak dependence on both the separation and related molecular conformation. However, if the contraction of the gap between the electrodes is accommodated by tilting the molecule, the conductance will increase with the tilting angle, in line with experimental observations. It is demonstrated that the effect of tilting on transport can be interpreted in a similar way to the case of the stretching the junction with a molecule in an upright position. The lowest conductance was observed for the equilibrium gap geometry. With the dominant transport contribution arising from the ? system of the frontier junction orbitals, all the predicted increases in the conductance arise simply from the better band alignment between relevant frontier orbitals at the nonequilibrium geometries at the expense of weaker coupling with the contacts.
PUBLISHED
Keywords: Atomic, molecular and chemical physics; gap geometry; Nanoscience & Materials